Quantum Game Simulation - Alonso-Sanz, Ramon (Emergence, Complexity and Computation, 2019)
This book addresses two disciplines that have traditionally occupied completely different realms: quantum information and computation, and game theory. Helping readers connect these fields, it appeals to a wide audience, including computer scientists, engineers, mathematicians, physicists, biologists or economists. The book is richly illustrated and basic concepts are accessible to readers with basic training in science. As such it is useful for undergraduate students as well as established academicians and researchers. Further, the didactic and tutorial-like style makes it ideal supplementary reading for courses on quantum information and computation, game theory, cellular automata and simulation.